1975
DOI: 10.1093/geronj/30.3.307
|View full text |Cite
|
Sign up to set email alerts
|

Age Differences in Backward Monoptic Visual Noise Masking

Abstract: An investigation of age differences in backward monoptic visual noise masking was carried out with young and old adult subjects. It was found that the older subjects were susceptible to the backward masking effect over significantly longer delays between the target and masking stimulus. The masking effect seems to be, at least in part, attributable to age changes in the central mechanisms concerned with perceptual processing which limit the rate at which stimuli can be "cleared" through the nervous system. Bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Consistent with this, the current results show that firsttarget accuracy is worst at the shortest SOA (66 ms), improving as the SOA increases to 100 and 133 ms; this is true both for the younger and older adults. There is also evidence in the literature that visual masking is stronger in older adults and that the effects of masking persist with longer periods of time between the stimulus and the mask (Di Lollo, Arnett, & Kruk, 1982;Kline & Birren, 1975;Kline & Szafran, 1975;Walsh, 1982). This increase in the strength and duration of masking may underlie the reduced first-target identification accuracy observed for the older adults.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this, the current results show that firsttarget accuracy is worst at the shortest SOA (66 ms), improving as the SOA increases to 100 and 133 ms; this is true both for the younger and older adults. There is also evidence in the literature that visual masking is stronger in older adults and that the effects of masking persist with longer periods of time between the stimulus and the mask (Di Lollo, Arnett, & Kruk, 1982;Kline & Birren, 1975;Kline & Szafran, 1975;Walsh, 1982). This increase in the strength and duration of masking may underlie the reduced first-target identification accuracy observed for the older adults.…”
Section: Resultsmentioning
confidence: 99%
“…Perception of a new signal would, therefore, tend to be slow, and capture of attention by feedback would thus be more likely to occur with repeated signals than with different ones. (3) The time required to form a visual percept has recently been shown to rise with age (Kline and Szafran, 1975;Walsh, 1976)and it may be supposed that, in consequence, the attention of older subjects is more likely than that of younger subjects to be captured by feedback from the response, especially when signals are repeated.…”
Section: Human Factorsmentioning
confidence: 99%
“…It has been reported, not only in vision, although the preponderance of the literature concerns that modality, but also in hearing and touch (Coltheart, 1980). Visual persistence lasts longer in older subjects (Amberson, Atkeson, Pollack, & Malatesta, 1979;Brozek & Keys, 1945;Kline & Birren, 1975;Kline & Szafran, 1975;McFarland, Warren, & Karis, 1958;Misiack, 1951). Mundy-Castle (1953) found that the EEG response to photic stimuli is prolonged as age increases.…”
Section: Sensory Persistencementioning
confidence: 99%